2020
DOI: 10.1007/s00425-020-03356-8
|View full text |Cite
|
Sign up to set email alerts
|

Diverse and dynamic roles of F-box proteins in plant biology

Abstract: The SCF complex is a widely studied multi-subunit ring E3 ubiquitin ligase that tags targeted proteins with ubiquitin for protein degradation by the ubiquitin 26S-proteasome system (UPS). The UPS is an important system that generally keeps cellular events tightly regulated by purging misfolded or damaged proteins and selectively degrading important regulatory proteins. The specificity of this post-translational regulation is controlled by F-box proteins (FBPs) via selective recognition of a protein-protein int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(52 citation statements)
references
References 271 publications
0
41
0
Order By: Relevance
“…The regulation of protein stability is critical in plant responses to environmental signals, which is largely mediated by the ubiquitin-proteasome system (UPS), especially the functions of E3 ligases as regulators of phytohormone signaling pathways for a coordinated response [ 135 ]. The CRGs included aspartyl protease (AT4G16563) and a set of U-box or F-box type E3 ubiquitin ligases, comprising PUB29 (AT3G18710), PUB45 (AT1G27910), RING/U-box superfamily protein (AT5G47610), SGR9 (AT5G02750), SNIPER1 (AT1G14200), EBF2 (AT5G25350), PP2-A14 (AT5G52120), KMD2 (AT1G15670), KMD4 (AT3G59940), F-box/kelch-repeat protein (AT1G14330), HUP6 (AT3G27220), and BTB/POZ domain-containing protein (AT2G30600), most of which have been documented to play diverse roles in plant development, stress responses, phytohormone signaling, and secondary metabolites [ 136 , 137 , 138 , 139 , 140 , 141 ]. Recently, it was reported that cAMP deficiency in tobacco BY-2 cells caused differential expression of many proteasome subunits [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…The regulation of protein stability is critical in plant responses to environmental signals, which is largely mediated by the ubiquitin-proteasome system (UPS), especially the functions of E3 ligases as regulators of phytohormone signaling pathways for a coordinated response [ 135 ]. The CRGs included aspartyl protease (AT4G16563) and a set of U-box or F-box type E3 ubiquitin ligases, comprising PUB29 (AT3G18710), PUB45 (AT1G27910), RING/U-box superfamily protein (AT5G47610), SGR9 (AT5G02750), SNIPER1 (AT1G14200), EBF2 (AT5G25350), PP2-A14 (AT5G52120), KMD2 (AT1G15670), KMD4 (AT3G59940), F-box/kelch-repeat protein (AT1G14330), HUP6 (AT3G27220), and BTB/POZ domain-containing protein (AT2G30600), most of which have been documented to play diverse roles in plant development, stress responses, phytohormone signaling, and secondary metabolites [ 136 , 137 , 138 , 139 , 140 , 141 ]. Recently, it was reported that cAMP deficiency in tobacco BY-2 cells caused differential expression of many proteasome subunits [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…The Arabidopsis genome contains over 700 genes encoding putative F-box proteins. SCFmediated protein degradation plays critical roles in many aspects of plant growth and development (12) . Here, we identify SCF AFF1 as a promoter of ARF19 destabilization to modulate auxin responses and plant development.…”
Section: Discussionmentioning
confidence: 99%
“…The molecular mechanisms by which HWS modulates miRNA levels are still unclear and the different phenotypes observed among orthologous mutants may be resulting from distinct, unrelated functions of the gene. HWS encodes an F-box protein, suggesting a function within Skip1-Cullin-F-box (SCF) complexes in protein degradation via the 26S proteasome machinery [ 13 ]. The FBK1 protein, encoded by one of the rice HWS orthologs, was shown to interact with a reductase involved in lignin synthesis to presumably tag it for degradation [ 11 ].…”
Section: Introductionmentioning
confidence: 99%